Investigation of Pedestrian Crossing Speeds at Signalized Intersections with Heavy Pedestrian Volumes. Issue 1 (January 2014) - Park, H. Joon; Yang, Weili; Yu, Weizhe; Wagner, Ilana; Ahmed, Shakil
The policy of the New York City Department of Transportation on the use of pedestrian crossing speeds is intended to provide sufficient time for pedestrians to cross the street and, thus, to support pedestrian safety at signalized intersections. This policy adheres to current guidelines provided in the Highway Capacity Manual 2010 and the Manual on Uniform Traffic Control Devices, which generally recommend the use of a fixed walking speed; however, pedestrian walking speeds at crosswalks vary depending on pedestrian density. As crosswalks become more crowded, pedestrian walking speeds become slower. The purpose of the study described in this paper, therefore, was to identify the need for and recommend a guideline for dynamic pedestrian walking speeds during pedestrian clearance intervals that fluctuated on the basis of how pedestrians behaved in crosswalks with various pedestrian densities. Such control could help provide appropriate pedestrian clearance intervals at crosswalks with distinctively high densities. This study modeled the relationships between pedestrian walking speeds and densities and between speeds and the proportions of pedestrian flows by direction at signalized intersections with heavy pedestrian volumes, as in central business district locations in New York City. On the basis of the relationships analyzed, speed and density levels were identified as measures of safety and congestion levels. Furthermore, the study showed that pedestrian crossing speeds within high-density crosswalks were affected by opposing pedestrian flows.